COMMUNITY MENTAL HEALTH CENTERS, TEENAGERS WITHOUT PARENTAL CARE AND THEIR CAREGIVERS, NEED AND REALITY - VILLAFANE-ALVA, José (2024)
The new model of bringing mental health services, the community model, started in 2012, focuses on the demands of the people in their social context, recovering the illness as well as promoting the wellbeing. The Community Mental Health Centers (CMHC) were born with the new model and are the liaison axis of all the mental health services in the catchment area. In this context, a high vulnerability group are the teenagers without parental care living in Residential Care Facilities (RCF), they have a high risk for development of mental disorders. Research bonding health and welfare public systems is scarce. In this qualitative research the points of view of the CMHC staff ofrepresentative regions of the country are taken, considering the difficulties in the work with the RCF and the lack of specific intervention programs even though the legislation exists. Finally, the opinion of the teen residents and their caregivers regarding the expectation of the mental health services provided are also taken.